Four Years of Yayasan Bumi Publikasi Nusantara’s Contribution to Advancing Knowledge and Supporting the Sustainable Development Goals (SDGs): A Bibliometric Perspective on ASEAN Journal for Science and Engineering in Materials - Srie Rosalin Nandiyanti (Bumi Publikasi Nusantara, 2025)
Since its establishment on 10 January 2022, Yayasan Bumi Publikasi Nusantara (BPN) has been dedicated to enhancing the quality and visibility of Indonesian scientific publications, aligning with the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 9 (Industry, Innovation, and Infrastructure). BPN currently manages nine international open-access journals through the Open Journal Systems platform. Among these, the ASEAN Journal for Science and Engineering in Materials (AJSEM) stands out as a leading journal, engaging authors from 17 countries and disseminating impactful theoretical and experimental research in material science. BPN has strengthened the national and global research ecosystem, fostered international collaboration, and promoted open science. This paper highlights BPN’s achievements, challenges, and strategic recommendations to advance its role in supporting global scientific progress and the SDGs. This study combines a descriptive overview with bibliometric analysis, examining publication trends, citation performance, and global collaboration patterns in material science.